Total Aerobic Bacterial Plate Counts (Apc) Of Raw Milk, Cottage Cheese And Curd Samples - Swarnakar, R.; Chhabra, D.; Sharda , R. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Total 150 samples comprising of 50 raw milk, 50 cottage cheese and 50 curd samples were collected and the aerobic plate count (APC) of each sample was determined. The average APC of milk samples was 19 x 104 cfu/ml, followed by 21 x 104 cfu/g of curd samples and 21.5 x 104 cfu/g of cottage cheese samples. The APC value of total 150 milk and milk product samples ranged from 11 x 104 cfu/ml/g to 29 x 104 cfu/ml/g with an average of 20 x 104 cfu/ml/g and the log10 cfu/ml/g value of APC is 6.9734.